Urine Analysis of Cat Utilizing the ThinkaÂ® Automatic Urine Analyzer as an Indicator for Uropoetic Disorders - Riwu, Katty Hendriana Priscilia; Karina, Soca; Afnani, Daniah Ashri; Yansri, Alifianita Anake; Kholik, Kholik; Khairullah, Aswin Rafif (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to determine the chemical content of the urine of local cats living freely around Mataram. The sample used was cat urine taken randomly. Twenty-five catsâ€™ urine samples were put into a sterile urine pot. Urine chemistry examination and observation were carried out using a urine analyzer strip to identify the levels of urine chemistry, namely nitrite, protein, pH, blood, ketones, bilirubin, and glucose. The examination was done by dipping the strip into each urine sample; the strip was taken and tapped on the tissue, then inserted into the urine analyzer machine. After the results are obtained, the machine will automatically issue the results of the urine chemistry analysis, reading the results for no more than 60 seconds. This study emphasizes observing the quantity or amount of substances and sedimentation in cat urine samples. All of the 25 samples examined were positive (100%) for nitrite, protein, ketones, and glucose levels. The results of the blood level examination in urine were negative in all samples, the examination of urine pH levels in 25 samples varied with an average pH of 6.84, and the examination of bilirubin levels was positive in 24 (96%) urine samples. From the examination of the samples, there were indications of disorders of the uropoetic system and bacteriuria in cat urine.